Laminin, laminin-entactin and extracellular matrix are equally appropriate adhesive substrates for isolated adult rat cardiomyocyte culture and experimentation. Issue 5 (3rd September 2018) - Lumkwana, D.; Botha, A.; Samodien, E.; Hanser, S.; Lopes, J.
ABSTRACT: Although techniques for isolating and culturing adult cardiomyocytes were developed four decades ago, it still remains a challenge to isolate high yields of healthy viable cardiomyocytes, to maintain them in culture, and to use them successfully in experiments. This is due to the difficulty in deciding which adhesive substrate and buffer composition to use. Therefore this study aimed to (1) identify a robust experimental buffer to sustain survival of cultured adult rat cardiomyocytes (ARCMs) during control normoxic conditions, and (2) to identify an adhesive substrate that provides optimal cell adherence, not only during normoxia, but especially during simulated ischemia-reperfusion (SIR) experiments. Adhesion and viability of ARCMs were evaluated on laminin, laminin-entactin (LE), and extracellular matrix (ECM) at concentrations between 25–200 ug/ml, in three different normoxic experimental buffers and under SIR conditions. Differences in normoxic buffer composition had no effect on the adherence of ARCMs, but had a significant effect on mitochondrial function and thus cell viability. HEPES buffered PBS supplemented with 10 mM glucose was not sufficient to sustain cell viability unless 2 mM pyruvate was added, yet a cocktail of PBS and M199 provided an even greater viability. Finally, laminin, LE, and ECM retained similar numbers of ARCMs per concentration, but only provided efficient adhesion at concentrations ≥ 100 ug/ml.